Inverting the bad debt ladder: Credit self-efficacy and healthier financial state - Blyth, David (Faculty of Commerce, 2023)
Levels of indebtedness amongst South African consumers are increasing year on year and the formal lending system is not structured or incentivised to reverse this. In lieu of fundamental change in regulation and to current institutionalised lending and debt collection practices, the best way to reverse the negative cycle of ever-increasing indebtedness is by shifting control to the consumer themselves. Industry collection mechanisms are functional and blunt, treating any arrear debt as ‘bad' and by association all indebted consumers are labelled ‘bad' with no recognition of the circumstance an individual might find themselves in. Covid has had a devastating effect on consumer psychology and the ability for individuals and households to meet their financial obligations. A more empathy-led approach to supporting indebted consumers is necessary. The aim of this study is to establish the most important factors within credit self-efficacy that enable certain consumers to make better credit decisions and reverse the downward, self-reinforcing spiral to greater indebtedness, It has supported the development of a business model aimed at making it attractive and profitable for the lenders to actively support the enablement of consumer capability in relation to credit. Using an online survey, a quota-controlled sample of n=874 consumers was achieved, adequately representing the adult population active in the formal South African credit market. Through the development of a structured equation model using n=794 of the collected data records, the study has found that the typical treatment of the indebted is ineffectual in helping consumers return to a healthier financial state. The perception that consumer desire of material goods alone drives poor credit behaviour and therefore greater levels of indebtedness is unfounded, as is the idea of profligate spending and its impact on credit behaviour. Living a good lifestyle is important to consumers and does affect credit behaviour but this does not translate into a significant effect on financial state. Rather, it is the combination of financial credit self-efficacy, financial confidence and financial management, as composite credit self-efficacy, that has a significant and strong influence on credit behaviour. In turn, credit behaviour as a mediating variable significantly and strongly influences financial state, more so than the direct effect of composite credit self-efficacy. Financial state also has a significant and extremely strong influence on composite credit self-efficacy, proving that a healthier financial state actually empowers greater consumer self-efficacy in relation to credit and financial matters. It is therefore incumbent on lenders of credit to have a more sensitive appreciation of consumer context and support consumers along their whole credit journey, by better understanding their personal circumstances, related psychosocial factors and how this affects their level of composite credit self-efficacy and credit behaviour. Future studies should concentrate on how credit self-efficacy can be instilled and tracked from an early age, especially amongst consumers who are new to the credit market, as data suggests that a single event can trigger a life-long journey down a ladder of increasing indebtedness.